Personalized 3D-printed endoprostheses for limb sparing in dogs: Modeling and in vitro testing. (September 2019) - Timercan, Anatolie; Brailovski, Vladimir; Petit, Yvan; Lussier, Bertrand; Séguin, Bernard
Highlights: Personalized endoprostheses and cutting guides reduce surgery time by 25–50%. Numerical model of a limb with prosthesis is validated by biomechanical experiment. To improve stress distribution, implant stiffness must be reduced to 25–50 GPa. Abstract: Osteosarcoma is the most common type of bone cancer in dogs, treatable by amputation or limb-sparing surgery. For the latter, commercially available plate – endoprosthesis assemblies require contouring, to be adapted to the patient's bone geometry, and lead to sub-optimal results. The use of additively-manufactured personalized endoprostheses and cutting guides for distal radius limb-sparing surgery in dogs presents a promising alternative. Specialized software is used for the bone structure reconstruction from the patient's CT scans and for the design of endoprostheses and cutting guides. The prostheses are manufactured from a titanium alloy using a laser powder bed fusion system, while the cutting guides are manufactured from an ABS plastic using a fused deposition modeling system. A finite element model of an instrumented limb was developed and validated using experimental testing of a cadaveric limb implanted with a personalized endoprosthesis. Personalized endoprostheses and cutting guides can reduce limb sparing surgery time by 25–50% and may reduce the risk of implant failure. The numerical model was validated using the kinematics and force-displacement diagrams of the implant-limb construct. The model indicated that a modulus of elasticity of an implant material ranging from 25 to 50 GPa would improve the stress distribution within the implant. The results of the current study will allow optimization of the design of the personal implants in both veterinary and human patients. Graphical abstract: Image, graphical abstract